An empirical analysis on outsourcing decision: the case of e-banking services. Issue 1 (12th February 2018) - Hanafizadeh, Payam; Zare Ravasan, Ahad
Abstract : Purpose: A multitude of factors influence the information technology outsourcing (ITO) decision. Organizations must systematically evaluate these factors prior to making the ITO decision. The purpose of this paper is to provide an in-depth analysis toward understanding the critical factors in affecting ITO decision in the context of e-banking services. Design/methodology/approach: The effect of technological, organizational, and environmental attributes on e-banking services outsourcing decision were investigated in this paper. The study was carried out using the quantitative research methodology based on a survey of 23 banks. The partial least squares technique was utilized as the method of data analysis. Findings: The results of the data analysis illustrated that nine out of 11 assumed factors (i.e. perceived complexity, perceived cost, service observability to the client, cultural fit between client and supplier, perceived loss of organizational knowledge, prior outsourcing experience, external pressure, market volatility, and suppliers' power) influence the outsourcing decision of e-banking services. The findings also confirmed that the nature of the service and client IT capabilities did not exert any influence on the outsourcing decision. Originality/value: The study is among the first kind of ITO decision research which empirically investigates the effect of service observability, cultural fit, perceived loss of organizational knowledge, external pressure, market volatility, and suppliers' power amongst other factors on the ITO decision. The findings from this study provide insights for the banks and service providers to better understand the factors affecting the outsourcing decisions of e-banking services in contexts of less developed countries. Implications based on a specific situation of the Iranian banking sector is also proposed.